ION-IMPRINTED POLYMER FOR CD(II) ION ANALYSIS USING FLOW INJECTION ANALYSIS (FIA) - Chairurrizky, Syifabudi
Anthranilic Acid (2-Aminobenzenecarboxylic acid) is a derivative compound of phenol that has carboxylic acid and amine groups at the ortho position. This compound is commonly used as a precursor compound in drug manufacturing. The carboxylic acid and amine groups present in aspartic antranilate are functional groups that act as electron-donating groups. Therefore, this compound can form complexes with cationic heavy metals. Heavy metals are pollutants that are still often found in the environment due to increased anthropogenic activities. Cd(II) heavy metal ions are one of the heavy metals frequently found in industrial wastewater. In this study, polymer imprinting of Cd(II) ions was conducted using aspartic antranilate (Cd-IPs) as the base material. Cd-IPs was then applied in batch adsorption and online pre-concentration system using flow injection analysis (FIA). The polymer was synthesized using formaldehyde as a cross-linking agent and characterized using Fourier Transform Infrared (FTIR) spectroscopy. The adsorption performance and the application of the online pre-concentration system were observed using a flame atomic absorption spectrophotometer (FAAS) by determining the concentration of Cd(II) ions before and after the addition of Cd-IPs. Cd-IPs is expected to adsorb Cd(II) ions through strong covalent interactions, making it suitable for online pre-concentration systems. Poly(aspartic antranilate-co-formaldehyde) imprinted with Cd(II) ions and NIP were successfully synthesized, resulting in yellow-colored solid products. Qualitative leaching studies showed that leaching was successfully performed using 1 M HNO3, and Cd-IPs contained a small amount of Cd(II) ions in its polymer cavities, as characterized by FTIR and SEM-EDS. Leaching studies indicated that 21 cycles were required to completely remove Cd(II) ions. The optimal adsorption conditions using Cd-IPs were found at pH 5 with a contact time of 45 minutes. Both polymers followed pseudo-second-order adsorption kinetics and Langmuir adsorption isotherm models. The breakthrough volume of the mini-column containing Cd-IPs was 0.62 mL for a Cd(II) concentration of 400 ?g L?1 , with the optimum eluent concentration being 2 M HNO3. Analytical parameter evaluation of the Cd-IPs-FIA-FAAS system showed good results with linearity in the range of 4 – 60 ?g L?1 ,